Making transnational feminism : rural women, NGO activists, and northern donors in Brazil - Thayer, Millie (New York : Routledge, 2010)
"Making Transnational Feminism takes the "ant's eye view" of global social movement relationships from the ground. Using ethnography, Thayer takes us inside transnational feminist alliances, viewing them from the local perspective of two women's movements in Northeast Brazil - one in the remote semi-arid interior and the other in Brazil's fourth largest city, Recife. She finds rural women and NGO feminists appropriating and translating global gender discourses, negotiating with each other over political resources, and strategizing to defend their autonomy from distant donors." "In the process, she argues, the Brazilian organizations help to constitute a transnational feminist political space-a "counterpublic," in which movements debate strategies, articulate new identities, and work to develop alternative social practices. Feminist alliances in this space are characterized by a precarious balance between solidarity and self-interest, collaboration and contention. At the turn of the twentieth century, as markets extended their reach into new regions and social sectors, they also threatened to reshape feminist relationships, undermining the very values on which they were founded. and pushing them toward competitive and instrumental behavior. Thayer shows us how feminist movements in Northeast Brazil struggled to sustain their alliances and to defend their endangered counterpublic against the long hand of the "social movement market.""--Jacket.
1 Introduction: Re-Reading Globalization from Northeast Brazil 1 -- 2 Uneasy Allies: The Making of a Transnational Feminist Counterpublic 35 -- 3 Translating Feminisms: From Embodied Women to Gendered Citizenship 53 -- 4 Negotiating Class and Gender: Devalued Women in a Local Counterpublic 83 -- 5 The Leverage of the Local: "Authentic" Rural Women in Global Counterpublics 110 -- 6 Feminists and Funding: Plays of Power in the Social Movement Market 128 -- 7 Movement or Market? Defending the Endangered Counterpublic 164 -- Methodological Appendix: Transnational Feminism as Field 170.
Includes bibliographical references (pages 205-223) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Rural women -- Brazil, Northeast -- Social conditions; Feminism -- Brazil, Northeast; Northeast Brazil; Brasilien -- Nordost; Feminism -- Brazil; Feminismus -- Brasilien; Globalisierung; Globalization -- Social aspects -- Brazil; Soziologie; Electronic books